Transient mode features at sapphire growing by horizontal directional crystallization - Barannik, S.V.; Kanischev, V.N.; Nizhankovsky, S.V.; Stepanenko, A.M. (Functional Materials, 2009)
The behavior of the crystal/alumina melt boundary has been studied at the start and final stages of sapphire growing by horizontal directional crystallization. At a constant pulling speed of the crystal into the cold zone, the time dependence of the melt crystallization rate may behave nonmonotonically. The crystallization front oscillations in the initial transient process that was predicted by numerical simulation has been confirmed experimentally.